2022
DOI: 10.3389/fimmu.2021.746998
|View full text |Cite
|
Sign up to set email alerts
|

Causal Relationship Between Gut Microbiota and Autoimmune Diseases: A Two-Sample Mendelian Randomization Study

Abstract: BackgroundGrowing evidence has shown that alterations in gut microbiota composition are associated with multiple autoimmune diseases (ADs). However, it is unclear whether these associations reflect a causal relationship.ObjectiveTo reveal the causal association between gut microbiota and AD, we conducted a two-sample Mendelian randomization (MR) analysis.Materials and MethodsWe assessed genome-wide association study (GWAS) summary statistics for gut microbiota and six common ADs, namely, systemic lupus erythem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
116
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(160 citation statements)
references
References 40 publications
1
116
0
Order By: Relevance
“…Over 90% of GM comprises 4 bacterial phyla, including Firmicutes and Actinobacteria ( 26 ). When GM dysbiosis occurs, it causes metabolic, immune, and neurological-related disorders ( 14 , 27 , 28 ). Nonetheless, the role of GM dysbiosis in the pathogenesis of DR remains elusive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over 90% of GM comprises 4 bacterial phyla, including Firmicutes and Actinobacteria ( 26 ). When GM dysbiosis occurs, it causes metabolic, immune, and neurological-related disorders ( 14 , 27 , 28 ). Nonetheless, the role of GM dysbiosis in the pathogenesis of DR remains elusive.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to randomized controlled studies, Mendelian randomization (MR) studies prevent the possible effects of confounding factors (e.g., diet) and reverse causality, using genetic variation instead of exposure to assess causal associations with outcomes. Studies using MR analysis to explore the causal relationship between GM and autoimmune diseases ( 14 ) and neuropsychiatric conditions have matured ( 15 ). Nonetheless, the mechanisms by which DR applies MR analysis remain unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…Because the allocation of genotypes from parent to offspring is random, the association between genetic variants and outcome is not affected by common confounding factors, and a causal sequence is reasonable [ 24 ]. MR has been widely applied to explore the causal association between gut microbiota and diseases, including metabolic diseases [ 25 ], autoimmune diseases [ 26 ], and rheumatoid arthritis [ 27 ]. In this study, using the genome-wide association study (GWAS) summary statistics from the MiBioGen and FinnGen consortiums, a two-sample MR analysis was conducted to evaluate the causal association between gut microbiota and PE.…”
Section: Introductionmentioning
confidence: 99%
“…After quality control, 10 SNPs were obtained to predict EIF4EBP (Supplementary Table 1 ). IVW showed that EIF4EBP was positively associated with cataract, and the result of MR. RAPS was similar (Table 1 ), which strengthened the confidence of the true causal associations[ 46 ]. Meanwhile, the association remained directionally consistent in weight median, whereas MR-Egger showed no association between mTORC1-dependent protein level of EIF4EBP with cataract (Table 1 ).…”
Section: Resultsmentioning
confidence: 83%